Greenwashing and Environmental Sustainability of European Automotive Firms - Koišová, Eva; Houska, Daniel; Andreisová, Lucie; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines whether the environmental ESG strategies of Volkswagen Group and Renault Group represent authentic sustainability practices or show indicators of greenwashing. Using a qualitative comparative case study and ESRS E1 alignment analysis, it evaluates the transparency, credibility, and completeness of their environmental disclosures. Based on these findings, the thesis proposes how both companies can more effectively integrate sustainability into their export strategies to enhance credibility and competitiveness in international markets.
Vedoucí práce: Daniel Houska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses